Juridical analysis of the regulation of fishery resources in the Indonesian exclusive economic zone - Nova, Sri Asih Roza; Isra, Saldi; Ferdi, Ferdi; Husin, Sukanda (Linguistics and Culture Review, 2021)
As an archipelagic country, Indonesia has a wealth of living and non-biological natural resources, especially in its exclusive economic zone, specifically in this zone, there are an abundant wealth of fishery resources, but the economy and welfare level of traditional Indonesian fishers are still below the poverty line, in addition to the management of exploration and exploitation of fishery resources, Indonesia faces various problems, one of which is a problem with legal provisions. Therefore, researchers will analyze legal problems in managing fishery resources in this study's exclusive Indonesian economic zone. To answer the questions in this study, the authors used normative juridical research methods, and the results of the analysis were described using qualitative methods. After reviewing the literature, the study results indicate that legal problems in the fisheries sector are due to overlapping regulations and conflicting regulations. For this reason, in this study, the authors suggest the need to revitalize the law in the fisheries sector by harmonizing the law.